Constraint Programming approach based Virtual Machine Placement Algorithm for Server Consolidation in Cloud data center - Selvi, C. Pandi; Sivakumar, S (International Journal of Computer Sciences and Engineering, 2025)
Server consolidation has recently become a major issue in cloud data centers. Energy efficiency is a key aspect in solving server consolidation issues. Virtual machine placement algorithms play an important role in maximizing the resource utilization may lead to energy efficiency. Constraint programming is an approach used to find the available servers and migrate these servers to the virtual machines by treating them as constraints to find optimal solution. The objective function of this work is to increase resource utilization by minimizing the number of active physical machines and decrease the search time of constraint solver for better energy efficiency. In this paper a Best Fit Resource Utilization ( BFRU) algorithm is proposed for virtual machine placement, it use best fit algorithm technique. However, virtual machine placement problem is formulated as a variant of multidimensional bin packing problem and then a constraint solver is used to solve the problem using the dataset collected from Amazon EC2.The proposed BFRU algorithm implemented through NetBeans IDE to evaluate the data collected. The simulation result shows that constraint programming based virtual machine placement algorithm BFRU can effectively reduce the energy consumption with respect to memory.